2018
DOI: 10.1088/1361-648x/aaeb72
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics on next-neighbour distances in liquid and undercooled gallium

Abstract: Density fluctuations of liquid and 20 K undercooled gallium have been studied by neutron spectroscopy. The decay of density fluctuations has been recorded at the structure factor maximum over a wide temperature range up to twice the melting temperature. The amplitude of the scattering function falls off with rising temperature in a nonlinear way with a changing slope around 1.5 T melting . The derived generalized longitudinal viscosity shows an upturn with decreasing temperature in the same temperature range. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 78 publications
2
6
0
Order By: Relevance
“…This change in relaxation times accompanies the changes in the lineshape, evidenced through the lineshape parameter β. We conclude from these results and from the previous observations [28] on the amplitude S(Q 0 , ω = 0) and the generalized longitudinal viscosity η l (Q 0 ) that in the temperature range of 1.2-1.5 T melting the collective dynamics of liquid gallium is altering.…”
Section: Resultssupporting
confidence: 77%
See 4 more Smart Citations
“…This change in relaxation times accompanies the changes in the lineshape, evidenced through the lineshape parameter β. We conclude from these results and from the previous observations [28] on the amplitude S(Q 0 , ω = 0) and the generalized longitudinal viscosity η l (Q 0 ) that in the temperature range of 1.2-1.5 T melting the collective dynamics of liquid gallium is altering.…”
Section: Resultssupporting
confidence: 77%
“…The rate decreases considerably when the main structure factor peak S(Q 0 ) is reached, the deGennes narrowing. Scattering experiments in the energy domain demonstrated that a fit with a single Lorentzian is a good description of the lineshape at the structure factor maximum [28]. However, measurements with good statistics and a wide dynamic range indicated deviations from the single Lorentzian model [12,13].…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations